Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1007/978-3-319-28460-6_5
|View full text |Cite
|
Sign up to set email alerts
|

An Axiomatic Approach to Support in Argumentation

Abstract: OATAO is an open access repository that collects the work of Toulouse researchers and makes it freely available over the web where possible. This is an author-deposited version published in : http://oatao.univ-toulouse.fr/ Eprints ID : 15488The contribution was presented at : http://homepages.abdn.ac.uk/n.oren/pages/TAFA-15/ Any correspondence concerning this service should be sent to the repository administrator: staff-oatao@listes-diff.inp-toulouse.fr An axiomatic approach to support in argumentationClaudett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…This last result-which requires a relatively complex argumentative representationopens up an interesting avenue for future work, namely in determining which nonmonotonic logics can be easily captured through standard formal argumentation techniques, and which require additional rules or axioms in order to be represented. We note that on the argumentation side, work on bipolar argumentation (e.g., [9]) has considered introducing additional defeats between arguments based on some notion of support, and we intend to investigate how the additional defeats we introduced can be categorized in such frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…This last result-which requires a relatively complex argumentative representationopens up an interesting avenue for future work, namely in determining which nonmonotonic logics can be easily captured through standard formal argumentation techniques, and which require additional rules or axioms in order to be represented. We note that on the argumentation side, work on bipolar argumentation (e.g., [9]) has considered introducing additional defeats between arguments based on some notion of support, and we intend to investigate how the additional defeats we introduced can be categorized in such frameworks.…”
Section: Discussionmentioning
confidence: 99%
“…For this edge, the Neither Agree nor Disagree level of agreement is the most common value, both in the total and in the core sample. 17 G-test for independence yields G-value 208.01 with 6 degrees of freedom and p-value less than 2.2 × 10 −16 . This result was obtained using the library Deducer (likelihood.test function) in R. 18 G-test for independence yields G-value 175.33 with 6 degrees of freedom and p-value less than 2.2 × 10 −16 .…”
Section: 1 Effect Of a Relation On Its Sourcementioning
confidence: 96%
“…The reason for this is two-fold. First of all, there is no consensus as to which indirect conflicts should be associated with a given specialized form of support, such as deductive or necessary [49,17,54]. Second of all, we are not aware of any empirical study verifying that people indeed associate with a given type of support the indirect attacks ascribed to it in theory.…”
Section: Argument Graphsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, in the last years, recent studies on argumentation have shown that a support interaction may exist between arguments, this kind of relation represents some real world situations. In this sense, several formal approaches were considered such as deductive support, necessary support and evidential support [10,11,12,13], where a classical argumentative framework is enhanced to model a positive and negative interaction between arguments. In special, a simple abstract formalization of argument support is provided in the framework proposed by Cayrol and Lagasquie-Schiex in [10], called Bipolar Argumentation Framework (BAF), where they extend Dung's notion of acceptability by distinguishing two independent forms of interaction between arguments: support and attack.…”
Section: Introductionmentioning
confidence: 99%